Effects of injection molding parameters on cellular structure of roofing tiles composite. (2021) - Ahmad, Mumtaz; Waseem, Mohammad
Abstract: A hybrid composite consists of two or more types of reinforcements to make a composite depending on the application. Due to their high specific stiffness and strength, fibre-reinforced polymeric composites are widely applied in diverse applications. The beauty of this combination (fiber–matrix system) is that it provides high fracture toughness at high strength levels, a property impossible to obtain with a single material. In this paper, the processing of polystyrene-based matrix composite (roofing tiles) is presented. Tensile testing of the specimen is performed on an Instron Testing Machine. The fabricated composites having a microcellular structure were used for making roofing tiles and building structures. The prepared samples were checked for hardness. These cellular composites are characterized by average cell diameter and cell density. The Microcell Distribution Index (MDI) has been proposed for the characterization of cell morphology. Microcellular injection moulded specimens for roofing tiles were analyzed for the effects of moulding parameters over microcell distribution. Various injection moulding parameters were analyzed for their effect over cell morphology characterized by cell size, cell density and distribution pattern. Effects of injection rate, back pressure, melt temperature and barrel residence time are being studied in the present work.